80 years of protecting children's health (to the anniversary of the formation and development of the Department of Children's Infectious Diseases named after Professor S. D. Nosov of the Ivanovo State Medical Academy) - V. F. Balikin (LLC "Diagnostics and Vaccines", 2023)
The article presents the history of the development of the Department of Children's Infectious Diseases named after Professor S.D. Nosov of the Ivanovo State Medical Academy. The department was created in 1943 on the basis of the 2nd infectious diseases building of the First City Clinical Hospital in Ivanovo. For 80 years, the staff of the department has preserved and continued the scientific and pedagogical traditions in training qualified personnel for Russian healthcare and preserving the health of children.